Development of a welfare assessment tool for tourist camp elephants in Asia - Raman Ghimire; Janine L. Brown; Chatchote Thitaram; Sharon S. Glaeser; Kannika Na-Lampang; Pawinee Kulnanan; Pakkanut Bansiddhi (PeerJ)
Background Approximately one-third of Asian elephants are managed under human care, participating in educational, cultural, religious, and tourist activities. Management conditions vary considerably among venues, raising questions about whether welfare needs are consistently being met, particularly for Asian tourist camp elephants. To evaluate the well-being of elephants engaged in tourist activities, an evidence-based tool is needed for routine assessments to identify potential welfare risks, aid in the development of better camp standards, and enable caretakers to address specific concerns. While many animal welfare tools exist, none have been designed to consider specific environments and management practices faced by elephants living and working in tourist camps. Methods Using direct observations and interviews, the Elephant Welfare Assessment Tool (EWAT) was developed for tourist camp elephants using the Five Domains Model as a framework. Measures were selected based on peer-reviewed literature, existing standards and guidelines, and opinions from animal welfare experts working with zoo and tourist camp elephants. The EWAT differs from existing tools by including criteria on work activities and restraint methods (e.g., chaining and ankus use), factors common in Asia but not often encountered by western zoo elephants. Measures were scored using a 0–2 Likert Scale. The tool was tested in Thailand and determined by calculating a content validity index (CVI) and conducting inter-rater and test-retest reliability tests. Results The initial tool included 18 animal-based and 21 resource-based measures across four domains: Nutrition (n = 5), Environment (n = 14), Health (n = 10), and Behavior and Mental State (n = 10). Index scores of content validity (CVI) (Item CVI (0.83), Scale CVI/Average (0.98), and Scale CVI/Universal (0.89)) were high. Measures scoring less than 0.83 were removed: the opportunity to mate, the mahout-elephant relationship, and mahout job satisfaction. The final tool consisted of 42 questions related to 36 measures, including 18 animal-based and 18 resource-based measures within the Nutrition (n = 5), Environment (n = 11), Health (n = 10), and Behavior and Mental State (n = 10) domains. Intraclass correlation coefficients (ICC) for inter-rater reliability (0.78–0.90, p < 0.05) and test-retest (0.77–0.91, p < 0.05) analyses conducted at two camps showed good agreement. Conclusions This new assessment tool (EWAT) is a context-specific, holistic method designed to offer a practical means of conducting individual and institutional-level assessments of elephant welfare in tourist camps. It is based on the Five Domains Model using reliable and validated animal- and resource-based measures, data collection through direct observation and interviews, and a numerical scoring system. The tool includes several criteria applicable to tourist rather than zoo venues to make it more relevant to the challenges faced by working elephants in Asia.